Os impactos socioeconômicos da mineração em Juruti - PA - GALÚCIO, Paulo Vitor Batista (Universidade Federal do Oeste do Pará, 2024)
The present work verified the socioeconomic impacts that occur in a municipality in the west of Pará, after the installation of a mining enterprise in its territory. The impacts arising from the installations of mining companies can be both positive and negative. Analyzing such impacts that occurred in the municipality of Juruti-PA, from 2009 onwards, when bauxite exploration began at the site. The objective is to verify the alterations that the municipality suffered after the arrival of the mining company. The information was obtained through bibliographic research and responses obtained in a questionnaire that was answered by a sample of the local population. The population, when questioned about the main positive aspects of mining for Juruti, considered that the greatest benefit for the municipality was in the economic sector and then in the social sector. As for the negative impacts, the most cited was the environmental aspect, followed by those who thought that mining did not bring negative impacts to the municipality. Based on this information, it can be concluded that for the municipality of Juruti, mining is seen as positive by the majority of the local population.